Exercise suppresses DEAF1 to normalize mTORC1 activity and reverse muscle aging - Sze Mun Choy; Kah Yong Goh; Wen Xing Lee; Weiyi Jiang; Qian Gou; Priya D. Gopal Krishnan; Shi Chee Ong; Kenon Chua; Nathan Harmston; Hong-Wen Tang (Proceedings of the National Academy of Sciences, 2025)
Skeletal muscle is essential for movement, respiration, and metabolism, with mTORC1 acting as a key regulator of protein synthesis and degradation. In aging muscle, mTORC1 becomes overactivated, contributing to sarcopenia, though the mechanisms remain unclear. Here, we identify DEAF1, a FOXO-regulated transcription factor, as a key upstream driver of mTORC1 in aged muscle. Elevated Deaf1 expression increases mTOR transcription, leading to heightened mTORC1 activity, impaired proteostasis, and muscle senescence. Remarkably, exercise suppresses Deaf1 expression via FOXO activation, restoring mTORC1 balance and alleviating muscle aging. Conversely, FOXO inhibition or Deaf1 overexpression blocks exercise benefits on muscle health. These findings highlight DEAF1 as a critical link between FOXO and mTORC1 and suggest that targeting the FOXO–DEAF1–mTORC1 axis may offer therapeutic potential to preserve muscle function during aging.